Editorial AI Integration in Developing Newsrooms Evidence from Nigerian Newspapers - Paulinus C. Ogbodo; Terve M. Akase; Muhammad S. Rabiu (Feedback International Journal of Communication, 2026)
Artificial Intelligence (AI) is increasingly transforming journalism practices globally, yet empirical evidence regarding its integration in developing-country newsrooms remains limited. This study examines the integration of AI in editorial operations within Nigerian newspaper organizations, focusing on its contributions to editorial efficiency, patterns of adoption, and barriers to implementation. Guided by Rogers' Diffusion of Innovation (DOI) theory, the study employed a mixed-methods research design involving quantitative surveys and qualitative interviews. Data were collected from journalists working in three major Nigerian newspapers namely Leadership, Daily Trust, and Daily Sun with 141 valid questionnaire responses analyzed alongside in-depth interviews with editorial personnel. The findings reveal that AI integration significantly enhances editorial efficiency and accuracy, particularly in fact-checking (Mean = 3.37), reduction of human errors (Mean = 3.26), and improved news production efficiency (Mean = 3.15). However, AI adoption remains selective and limited primarily to supportive editorial functions, while advanced applications such as real-time automated news generation remain minimally utilized (Mean = 1.58). The study further identifies significant barriers to AI integration, including concerns about reduced journalistic creativity (Mean = 3.05), inadequate funding and infrastructure (Mean = 3.04), fears of job displacement (Mean = 2.99), ethical concerns regarding misinformation and editorial integrity (Mean = 2.92), and insufficient technical expertise (Mean = 2.90). The findings suggest that AI currently functions as an augmentative technology that supports rather than replaces journalists. The study concludes that successful AI integration in developing newsrooms requires strategic investment, continuous professional training, institutional support, and robust ethical governance frameworks to facilitate responsible and sustainable digital transformation in journalism.